Menyoal Hak Berkampanye Presiden Pada Pilpres 2024 Dari Perspektif Etika Pancasilan Dan Islam - Dian Kus Pratiwi; Ahmad Sadzali (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This paper discusses President Joko Widodo's campaign practices in the 2024 election by highlighting ethical issues from the perspective of Pancasila and Islamic Ethics. As head of state, President Jokowi has a strategic position that demands moral exemplarity, political neutrality, and commitment to social justice. In practice, Jokowi on the one hand shows a positive attitude by rejecting the politicization of identity, religion, and intolerance that have the potential to damage the unity of the nation. However, on the other hand, his statement that the president is allowed to campaign and take sides, support for his son's candidacy as a vice presidential candidate, and the massive distribution of social assistance during the election period have raised ethical criticism. From the perspective of Pancasila Ethics, these steps cause conflicts with popular values, social justice, and the principle of unity. Meanwhile, Islamic Ethics which emphasizes justice ('adl), trust, honesty (ṣidq), and leadership that is beneficial to the ummah considers that these practices have the potential to contain conflicts of interest and obscure the mandate of office. Thus, President Jokowi's campaign reflects the dialectic between efforts to maintain political stability and national unity with ethical problems related to neutrality, justice, and leadership morality. This study emphasizes the importance of Pancasila and Islamic ethics as normative guidelines in maintaining the integrity of Indonesian democracy.